MARKETING STRATEGY ANALYSIS IN A GLOBAL MARKET - Muhammad Ilham Wardhana Haeruddin; Muh. Ichwan Musa; Agung Widhi Kurniawan (Journal Management & Economics Review (JUMPER), 2023)
This study uses qualitative research, analysis of the author's point of view, and relevant literature citations, expert opinions, and previous findings to support their arguments. This article explains how marketing strategies are practiced in Indonesia's global or international market. As we already know that global promotion is an act of demonstrating global marketing that a company has with a global advertising strategy, global business sectors, global items and global standards in various locations. Another challenge for companies using promotional strategies is globalization. companies have to compete with companies that have a lot of money and high-quality goods as a result of globalization. Indonesia has been a controversial target market to date. All leaders must concentrate on the global climate due to globalization and market competition. The purpose of this study is to determine the driving factors that influence marketing strategies in the Indonesian market and the company's development in the global market